Relationship between monocyte/macrophage activation marker soluble CD163 and insulin resistance in obese and normal-weight subjects - Zanni, Markella V.; Burdo, Tricia H.; Makimura, Hideo; Williams, Kenneth C.; Grinspoon, Steven K. (Clinical endocrinology (Oxford), 2012)
Summary Context  The relationship of monocyte/macrophage activation to insulin resistance in obesity is unknown. Objective  To investigate a marker of macrophage activation, soluble CD163 (sCD163), in relationship to insulin resistance and metabolic parameters in obese and normal‐weight subjects. Design and Participants  Ninety‐five healthy subjects (65 obese and 30 normal‐weight) were studied. Plasma concentrations of sCD163 were assessed, as well as markers of glucose homeostasis, anthropometrics, cytokines and adipokines. The relationships between sCD163 and these parameters were investigated, and multiple regression modelling assessing the contribution of sCD163 to insulin resistance (HOMA‐IR) was performed. Results  Soluble CD163 was significantly increased in obese subjects compared with normal‐weight controls [974 (657, 1272) ng/ml vs 599 (423, 892) ng/ml, median (IQR); P < 0·0001]. sCD163 was strongly associated with HOMA‐IR (Spearman’s ρ = 0·37, P = 0·0003) and other metabolic parameters. In multiple regression modelling for log HOMA‐IR, sCD163 remained significantly associated (P = 0·005) controlling for known mediators of insulin resistance including age, gender, visceral adiposity and inflammatory markers (model R2 = 0·54, P < 0·0001). Additional nested multiple regression models for log HOMA‐IR showed that sCD163 added more than other adipokines and inflammatory markers to the prediction of HOMA‐IR. Conclusions  Monocyte/macrophage activation, as reflected by sCD163 levels, is strongly associated with HOMA‐IR in normal‐weight and obese subjects after controlling for known mediators of insulin resistance. Moreover, sCD163 adds to standard risk markers for predicting insulin resistance. These data suggest that monocyte/macrophage activation may be an important determinant of insulin resistance in obesity.